Moving in and out of public geriatric care in Sweden - Daniel Hallberg; Mårten Lagergren (Uppsala University, Department of Economics, 2007)
In this paper we present empirical results concerning the interplay between the development of dependency in activities for daily living (ADL),the informal support from a partner, and the mode of public old age care (OAC) services among the very old (75+). We also study excess-mortality conditional on the mode of OAC. Three forms of publicly provided OAC are distinguished: independent living in ordinary home without public support, independent living in ordinary home or special accommodations with home help and home health care, and living in special accommodations with round-the-clock-care. Our results suggest, given the level of ADL and age, that the propensity to move to a more intensive mode of care was higher for women compared to men. There was, however, also an effect of the availability of informal care support that moved in the opposite direction; men with a partner were more likely to move from home-help service to a living in special accommodation, while women with a partner were more likely to remain with the same care mode than women without a partner. We also find a lower mortality among cohabitants with home-help services, while it is higher among cohabitants with special accommodation. Our estimates furthermore show the importance of removing the influence of unobserved heterogeneity.
urn:nbn:se:uu:diva-25387
Keywords: I12; I18; J14; 330; old age care; mortality; informal support from a partner; Altenhilfe; Langzeitpflege; Altenheim; Sterblichkeit; Schweden